V-030 LAPAROSCOPIC TRANSABDOMINAL PREPERITONEAL REPAIR OF A RIGHT SPIGELIAN HERNIA USING BIOSYNTHETIC (N-BUTYL CYANOACRYLATE) GLUE FOR MESH FIXATION AND PERITONEAL FLAP CLOSURE. (13th October 2022) - Chatzimavroudis, G; Kyriakidou, D; Hadjichristou, E; Tsompanis, D; Atmatzidis, S; Raptis, D; Kiroplastis, K; Papaziogas, V
Abstract: Spigelian hernia consists one of the most uncommon anterolateral abdominal wall hernias (<1%). The defect occurs at the spigelian fascia which is located lateral to rectus abdominis muscle along the linea semilunaris and is comprised of the transversus abdominis and internal oblique aponeuroses. Most commonly the defect is located at or below the level of arcuate line. Its diagnosis may be challenging because the aponeurosis of external oblique remains intact, leading to an intraparietal hernia, with no obvious bulge on inspection or even palpation of the abdominal wall in many cases. Computed tomography (CT) is the most reliable imaging method to diagnose a spigelian hernia. Due to the high risk of strangulation, surgery should be advised to all patients with spigelian hernia. Surgery can be performed either by open or by minimally invasive techniques. In this video we present the case of a 54-year-old female patient suffering from a symptomatic right spigelian hernia. The diagnosis was suspected during clinical examination and was confirmed with CT. The patient underwent a laparoscopic transabdominal preperitoneal repair. During the procedure, a peritoneal flap was created; the content of the hernia sac, composed from preperitoneal fat, was completely reduced; the defect was closed with 2/0 PDS sutures; a PVDF mesh, measuring 14 cm by 12 cm, was placed in the preperitoneal area and fixed with N-butyl cyanoacrylate glue; the peritoneal flap was closed also with glue. The patient had an unremarkable postoperative period and was discharged on the first postoperative day in good clinical condition.